An Alarming Hazard in The Community Using Aluminium in Day-to-Day Life on The Basis of Toxic Effects on The Liver of Abino Rats by Ingestion of Aluminium - Deepa Rani Agarwal; Sandeep B. Gupta (Medsci Publications, 2010)
Aluminium is widely used in medicines, as food additives, as water purification agent, as in the making of household cookware and storage utensils. Aluminium can get into the human beings via digestive tract or via lungs or through parenteral route. Absorption of aluminium depends upon the chemical forms of aluminium taken up and pH values in GIT. In acidic medium, absorption becomes higher. Aluminium hydroxide and chlorides are absorbed more efficiently than its phosphorus and fluorine compounds. The aluminium content of organs like liver and spleen increased in animals kept on an iron deficient diet1. As aluminium is stored mainly in the liver2, the present work is conducted to study the morphological changes in the liver produced by aluminium chloride (AICI3). 20 inbred adult albino rats weighing 150-200gm each were administered 37.5mg per day of aluminium chloride orally for 21 days with maintenance of 20 similar controls. A small piece of liver tissue was processed for paraffin sections. 7 µ thick sections were stained with hematoxylin and eosin stain and observed under light microscope. The changes were observed at tissue and cellular level along with general architectural derangement, degenerative changes and nuclear variations such as karryorrhexis, pyknosis. These findings are highly suggestive of toxic hepatitis.